2021
DOI: 10.1016/j.jaim.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the use of traditional complementary and alternative medicine amongst cancer patients in a tertiary care center in Kerala, India

Abstract: Background Unmet needs of cancer patients prompt them to seek care from Traditional, Complementary and Alternative Medicine (TCAM) practitioners. Objective To investigate the prevalence of TCAM use in a multi-specialty tertiary cancer center in South India. Materials and methods A cross-sectional survey of cancer patients who used TCAM during the study period. The patients were recruited based on covenience sampling method. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…In the literature, it is stated that health professionals do not have enough information about the use of CAM and they reject the use of CAM [33, 34]. However, in studies in India (71%) [31] and Australia (68%) [6] the rate of disclosing the use of CAM to their doctor is higher than in our study. The reason for this is thought to be the attitudes, cultural beliefs, and values related to the use of CAM in these countries.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In the literature, it is stated that health professionals do not have enough information about the use of CAM and they reject the use of CAM [33, 34]. However, in studies in India (71%) [31] and Australia (68%) [6] the rate of disclosing the use of CAM to their doctor is higher than in our study. The reason for this is thought to be the attitudes, cultural beliefs, and values related to the use of CAM in these countries.…”
Section: Discussioncontrasting
confidence: 80%
“…In a study in Saudi Arabia, 69.9% of cancer patients use CAM and mostly supplication (95.5%) [5]. In a study in India, 34.4% of cancer patients use CAM, and 36% use home remedies [31]. In Mongolia, 47.9% of cancer patients use CAM, and the most used CAM types are the products of animals and herbs [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have delved into the incidence of CAM use, healthcare professionals' attitudes toward CAM, and communication patterns that differ by nationality and cancer type [3][4][5][6][7][8]. In Korea, up to 85% of patients with cancer use one or more types of CAM [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Indian policy documents consider all of them under one umbrella and refer to them as AYUSH, 11 but not much is known about the extent, pattern, and costs associated with their usage. A study of cancer patients in Kerala found the use of AYUSH treatment along with allopathic treatment by patients; 12 another study looked at the utilisation of services and client satisfaction by patients attending a public AYUSH hospital in Delhi. 13 Even during the recent COVID-19 pandemic, studies found the use of yoga and self-care by respondents an effective strategy for mental and physical well-being.…”
Section: Introductionmentioning
confidence: 99%